Law Enforcement of Corruption Crimes in the State-Owned Enterprises Sector in Indonesia - Saputri, Atha Difa; Lee, John (Faculty of Law, Universitas Negeri Semarang, 2023)
Corruption often occurs in public service institutions, especially BUMN. This research was conducted to examine corruption in the BUMN sector with the Aristotelian ethical theory. Aristoteles theory of ethics serves to deliver humans to achieve the highest goals of their lives through ratios and make humans the main humans. This study uses a normative juridical research method in which the use of this method uses a conceptual approach and legislation. Regarding the conclusions obtained from this research, the definition of corruption is that it is a matter of moral deviation from a moral problem in humans. Therefore, law and the economy are not the main factors that encourage corruption in the BUMN sector. In the abuse of power in the BUMN sector which is the starting point for corruption, it is clear that there is a moral charge in this case, an element of intent. Thus, it is clear that corruption is closely related to moral issues in humans, in this case, BUMN officials. This is where the portrait of Aristotle's ethical philosophy is very visible in the phenomenon of corruption in the BUMN sector in Indonesia.